The life cycle in women-owned businesses: from a qualitative growth perspective. Issue 2 (8th June 2015) - Dalborg, Cecilia
Abstract : Purpose: – The purpose of this paper is to investigate women-owned businesses from a life cycle perspective and with a qualitative growth approach. Building on previous research that has identified qualitative growth platforms, this paper takes into account the time aspect and investigates perceived barriers and support needs inside different qualitative growth platforms. Design/methodology/approach: – The study took place in Sweden and is based on 191 women entrepreneurs in a first survey and 101 women entrepreneurs in a follow-up questionnaire three years later. To answer the research questions, descriptive frequency analysis and logistic regression analysis techniques have been used. Findings: – The motivation of growth changes throughout the life cycle, and women entrepreneurs move between different qualitative growth platforms when required building blocks of previous platforms have been established and secured. In this transfer of growth ambition, a significant correlation between business age and intrinsic growth aspiration was identified. Initially, growth is extrinsically motivated and later on in the life cycle, it is intrinsically motivated. In the late life cycle, the motivation is extrinsically motivated again. The results discern barriers to growth that hinder movement from extrinsic to intrinsic business platforms, and the author argues that the transfer of growth ambition from one growing platform to another requires different types of advice and support from the surrounding community. Research limitations/implications: – By broadening the view of growth to include both a quantitative and qualitative approach, it is possible to identify a widespread growth ambition in women-owned businesses which experience various barriers and supportive needs. Business programs that encourage exchange of experience among entrepreneurs in various growth platforms might be a way to overcome the perceived barriers. As women's businesses only receive a low proportion of the government funding, they are prevented from developing their growth ambitions. To ensure that all forms of growth are stimulated, different measures are required depending on which stage in their life cycle the women-owned businesses belong to. Originality/value: – By considering business growth from a qualitative perspective, barriers and needs that the traditional approach may overlook can be highlighted. For example, growth aspiration in terms of more employees will not be considered until the previously, qualitative growth platforms are established and secured. The support system, however, is designed to only favor growth in terms of employment, which results in difficulties to qualify for financial support.